Religious Values in the Ambengan Tradition in Kalangdosari Village, Ngaringan Subdistrict, Grobogan Regency: A Transformative Islamic Education and Local Wisdom Perspective - Sanoto (Lakpesdam PCNU Kota Salatiga, 2025)
The Ambengan tradition practiced during major Islamic commemorations (Hari Besar Islam, HBI) in Kalangdosari Village (Ngaringan Subdistrict, Grobogan Regency) is a religio-cultural practice that sustains local expressions of religiosity while functioning as a community-based medium for internalizing Islamic educational values. This article addresses three analytical foci: (1) how the forms, implementation mechanisms, and principal symbols of Ambengan (uba rampe, ritual offerings/arrangements) are understood within local socio-religious life; (2) which Islamic educational values faith (keimanan), morals/ethics (akhlak), and social values are internalized through the Ambengan procession and its supporting activity networks; and (3) the extent to which Ambengan operates as transformative Islamic education that strengthens social cohesion and religious moderation, including its socio-cultural and economic implications. The study employs a qualitative-descriptive approach using a document-based qualitative design, analyzed through thick description to capture symbolic meanings and thematic analysis to organize findings across the faith, morals, social domains. The findings indicate that Ambengan unfolds through a sequence of communal gatherings collective prayers/tahlil, sermons, and the distribution of ambeng (food hampers) conducted in rotation across hamlets. The uba rampe (rice, side dishes, whole cooked chicken ingkung, eggs, snacks, fruits, and occasionally clothing or money) functions as a symbolic system that links belief to social action through gratitude, almsgiving, and the strengthening of social ties. Faith values are cultivated through reinforcement of aqidah–sharia and narratives of prophetic exemplarity; moral values through communal etiquette, respect for moral authorities, and an ethics of giving; while social values are realized through reciprocity, solidarity, and the expansion of inter-hamlet/village networks that generate social capital (trust, norms of reciprocity, and social networks). However, Ambengan’s transformative capacity depends on sustained symbolic literacy and inclusive participation governance so that the tradition does not devolve into mere formal ceremony or status competition. The article recommends strengthening symbolic-literacy segments within the ritual sequence, integrating Ambengan with pengajian (Islamic study circles) as a sustainable value-education ecology, and applying “according to capacity” participation guidelines to safeguard ethical orientation and social cohesion; further research is encouraged through field ethnography to map variations in symbolic meanings and their impacts on religious character formation and community resilience.